PSYCHOLOGICAL BASES OF USING THE TECHNICAL EQUIPMENTS OF STUDIES FOR FUTURE LIBRARIANS - Маkеevа, Iryna I. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
In the lecture psychological bases of using technical equipments in systems of improvement of librarian employees qualification in higher educational establishments‘ libraries are illuminated.